Investigation upon the effect of the vaccination against the respiratory form of Aujeszky’s disease with a deletion mutant gE-/TK- vaccine in growing/fattening pigs - PAPATSAS (I.K. ΠΑΠΑΤΣΑΣ) J. C.; KYRIAKIS (Σ.Κ. ΚΥΡΙΑΚΗΣ) S. C.; PAPADOPOULOS (ΠΑΠΑΔΟΠΟΥΛΟΣ Ο.) O.; SARRIS (Κ. ΣΑΡΡΗΣ) K.; LEKKAS (Σ. ΛΕΚΚΑΣ) S. (Journal of the Hellenic Veterinary Medical Society, 2018)
In this trial study, the effect of the vaccination of growing/fattening pigs against Aujeszky’s disease virus (ADV) was investigated, in a farm placed in an endemic to ADV area. Three different trial groups of 11-week old growing pigs were vaccinated either once or twice or left unvaccinated. Comparisons between groups were made with respect to growth parameters, carcass quality, as well as pathological and bacteriological findings. All vaccinated animals had significantly better growth performance and carcass quality in comparison to the unvaccinated group, while no significant differences were observed between once and twice vaccinated animals. Lower lungs’ affection due to secondary pathogens was also observed in vaccinated groups when compared with the control group of pigs. Bacteriological examination revealed that the frequency of secondary pulmonary bacterial infections, such as Streptococcus suis and Pasteurella multocida was lower in vaccinated pigs compared to controls. It was concluded that single and probably double vaccination against ADV may improve growth performance and carcas quality and may reduce lung affection due to certain secondary pathogens, under the management conditions of the trial farm.